A Central Fiscal Stabilization Capacity for the Euro Area - Arnold, Nathaniel; Barkbu, Bergljot; Ture, H. Elif.; Wang, Hou. (Washington, D.C. : International Monetary Fund, 2018)
This note outlines a concrete proposal for a euro area central fiscal capacity (CFC) that could help smooth both country-specific and common shocks. Specifically, it proposes a macroeconomic stabilization fund financed by annual contributions from countries that are used to build up assets in good times and make transfers to countries in bad times, as well as a borrowing capacity in case an exceptionally large shock exhausts the fund's assets. To address moral hazard risks, transfers from the CFC-beyond a country's own net contributions-would be conditional on compliance with the EU fiscal rules. The note also discusses several features aimed at avoiding permanent transfers between countries and making the CFC function as automatically as possible-to limit the scope for disputes over its operation-both of which are important points to make it politically acceptable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet